Motion Analysis of Mixed Rehabilitation Process for Ankle Joint Auxiliary Rehabilitation Device based on Ball Pair Support - Wang Liangwen; Song Kangkang; Yue Lei; Shi Changmin; Du Wenliao (Jixie chuandong)
In order to realize ankle joint auxiliary rehabilitation,a kind of auxiliary device for ankle joint rehabilitation based on center ball pair is developed. The device adopts the center ball pair as the support,and 3S’PS’ branch chain as drive system. The rehabilitation device can form the three-dimensional motions of the working platform,which can realize auxiliary rehabilitation for ankle joint. The configuration of the device is introduced in detail,and movement process for the working platform to realize any posture is analyzed for the device. The calculation formulas of displacement,velocity and acceleration are deduced. On the basis of this,the concrete examples of motion analysis for device satisfying the motion constraint condition are given respectively,the basis for the design of the device control system is provided. The research process provide a reference for the motion analysis of similar structures.